Faktor Pengaruh Kepuasan Kerja Dan Loyalitas Kerja - Anifah Anifah; John EHJ FoEh (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
A person's job satisfaction is related to the person's perspective on the experience felt when working, while loyalty is a person's desire to stay and give his best performance for the organization. Both are very important because they will be closely related to a person's work output to the organization where he works. This study reviews the factors that influence job satisfaction and loyalty to an organization. This research is in the form of a literature review, where all the discussions in it come from various printed and electronic sources from various library sources. The analyzed factors consist of Salary, Age, Distance of Residence, Training, Performance Allowance, Performance Appraisal, Career Development, and Length of Service. This article was prepared with the aim of designing a hypothesis of the influence between variables so that it can be used as a basis for studies for future research. The results of this study, namely: 1) All factors analyzed have a significant effect on job satisfaction; 2) All factors analyzed have a significant effect on Loyalty. Based on the results that have been obtained, it is important for an organization to be able to make the factors that have been researched as material for consideration in carrying out the management of an organization. Suggestions for further research to be more comprehensive is to add other factors such as Work Environment, Leadership and Motivation as factors that influence job satisfaction and loyalty.